Ethnomatematics Exploration in Traditional Games As A Form Of Student’ Social Interaction - Moh Zayyadi; Sri Indriati Hasanah; Ema Surahmi (Universitas PGRI Madiun, 2018)
The purpose of the study is to know the principles and concepts of ethnomathematics in traditional games in elementary level of mathematics learning and to know the utilization of traditional games in students’ social interaction. Ethnomathematics is a mathematical practice in a cultural group. Mathematics as one of the subjects taught in elementary school to gain numeracy skills. In mathematics learning, informal knowledge of mathematics is developed into a mathematical concept through social interaction. Teachers and parents reintroduce traditional games to students in math learning activities in primary schools. this method aims to attract students to learn math by considering the material to be delivered and local culture. The form of social interaction of students in traditional games in learning mathematics is that students can become peer tutors of every game played along with mathematical concepts. The communication formed in the traditional game is one of the natural characteristics that occur, thus the traditional game can be used in the learning of mathematics as a form of social interaction between students based on the local culture.